Medical students' knowledge about COVID-19 and evaluation of the effectiveness of the applied preventive strategies - Kathie Sarzyńska; Eddie Czwojdziński; Amadeusz Kuźniarski; Sadri Rayad; Agnieszka Piwowar; Beata Jankowska-Polańska (BMC, 2022)
Abstract Background SARS-CoV-2 is a novel coronavirus which has caused a global pandemic. Due to the lack of available treatment for COVID-19 infections, prevention plays the most important role in combating the virus. Educational programs among students of medical faculties is necessary, because in the future they will act as health educators in the healthcare system. The aim of the study is to assess the students' knowledge as an initial stage to the implementation of further preventive strategies against the spread of SARS-CoV-2 virus infections and to the evaluation of the effectiveness of the implemented preventive measures by continuous monitoring of the number of implemented administrative procedures. Methods The study involved 482 students of medical faculties. Participants completed a questionnaire based on knowledge about the SARS-CoV-2 virus. Additionally, a number of preventive measures were introduced, including vaccination against COVID-19. During the entire period of the study, the number of administrative procedures (isolation and quarantine) were monitored. Results The results of the knowledge test about COVID-19 were generally low and amounted to 11.0 (SD = 2.2). Significant differences in knowledge about COVID-19 between students of particular medical faculties were found. The most appropriate answers to questions about the incubation time of the SARS-CoV-2 virus were given by students of medicine (55%), followed by nursing (42.14%) and pharmacy (26%) students. Nursing students were the most correct in identifying the 3 main symptoms of COVID-19 (91.07%), followed by students of medicine (85.83%), and finally dentistry (77.27%) and pharmacy (76.67%) students. The Median (IQR) of students quarantined or isolating during steps 1, 2, 3, and 4 was 117,5 (142); 40 (43); 38, (20); and 9,5 (15), respectively. Conclusion Students of certain faculties showed a low level of knowledge about transmission routes and procedures for dealing with a person suspected of being infected with SARS-CoV-2 or who has tested positive for COVID-19. Additional educational programs were conducted among medical students, along with other prevention strategies, which contributed to a decrease in the number of applied administrative procedures (isolation or quarantine).